Differences in mediterranean diet adherence on bmi, waist circumference, fat percentage, muscle mass in obesity - Endry Septiadi; Dinar Mutiara; Henny Juliastuti; Iis I Rakhmat; Dewi R Handayani (ACTA Medical Health Sciences, 2022)
Obesity is a multifactorial disease that occurs when there is an abnormal accumulation of body fat due to an imbalance between energy intake and energy expenditure. The prevalence of Riset Kesehatan Dasar in 2018 showed that 21.8% of the Indonesian population over 18 years is obese. One of the diets recommended by European Association for the Study of Obesity Community for obesity is the Mediterranean diet. This study aims to determine the difference of adherence level in the Mediterranean diet to nutritional status, and muscle mass in obese patients. The method used in this study is analytic observational with prospective cohort observations. Subjects in this study were 37 obese patients who were monitored for diet four times in one month with food frequency questionnaire and checked for BMI, waist circumference, body fat percentage, and muscle mass at the end of the month. BMI and body fat percentage were analyzed using the Anova test while waist circumference and muscle mass data were analyzed using the Kruskal Wallis test. The level of adherence to the Mediterranean diet has been shown to significantly affect BMI (p=0.008), waist circumference (p=0.042), body fat percentage (p=0.014), and muscle mass (p=0.009) in obese patients. This associated with the composition of Mediterranean diet which affects increase in thermogenesis, fat oxidation, anti-inflammatory, and increases satiety for a longer period. The results of this study support the hypothesis that there is the difference of adherence to the Mediterranean diet to nutritional status and muscle mass in obese patients. DOI : 10.35990/amhs.v1n1.p28-37 REFERENCES Sugondo S, Purnamasari D. Obesitas. Dalam: Setiati S, Alwi I, Sudoyo AW, editors. Buku Ajar Ilmu Penyakit Dalam. 6th ed. Jakarta: InternaPublishing; 2014. Chooi YC, Ding C, Magkos F. The epidemiology of obesity. Metabolism. 2019;92:p6–10. Harjatmo TP, Par’i HM, Wiyono S. Penilaian Status Gizi. Kementerian Kesehatan Republik Indonesia; 2017. Preedy VR. Handbook of Anthropometry: Physical Measures of Human Form in Health and Disease. Handb Anthr Phys Meas Hum Form Heal Dis. 2012:p1–3107. Ilman M, Zuhairini Y, Siddiq A. Correlation between Body Mass Index and Body Fat Percentage. Althea Med J. 2015;2(4):p575–8. Tomlinson DJ, Erskine RM, Morse CI, Winwood K, Onambélé-Pearson G. The impact of obesity on skeletal muscle strength and structure through adolescence to old age. Biogerontology. 2016;17(3):p467–83. Perkumpulan Endokrinologi Indonesia (PERKENI). Pedoman Pengelolaan dan Pencegahan Diabetes Melitus Tipe 2 Dewasa di Indonesia. 2019. Muscogiuri G, El Ghoch M, Colao A, Hassapidou M, Yumuk V, Busetto L. European Guidelines for Obesity Management in Adults with a Very Low-Calorie Ketogenic Diet: A Systematic Review and Meta-Analysis. Obes Facts. 2021;14(2):p222–45. Eric Zacharias MD. The Mediterranean Diet: A Clinician’s Guide for Patients Care. 2012. Chapter 2: p7-16. Sofi F, Cesari F, Abbate R, Gensini GF, Casini A. Adherence to Mediterranean diet and health status: Meta-analysis. BMJ. 2008;337(7671):p673–5. Boghossian NS, Yeung EH, Mumford SL, Zhang C, Gaskins AJ, Wactawski-Wende J, et al. Adherence to the Mediterranean diet and body fat distribution in reproductive-aged women. Eur J Clin Nutr. 2013;67(3):p289–94. Jura M, Kozak LP. Obesity and related consequences to ageing. Age (Omaha). 2016;38(1). Batsis JA, Zagaria AB. Addressing Obesity in Aging Patients. John. Physiol Behav. 2019;176(3):p139–48. Hodson L, Banerjee R, Rial B, Arlt W, Adiels M, Boren J, et al. Menopausal status and abdominal obesity are significant determinants of hepatic lipid metabolism in women. J Am Heart Assoc. 2015;4(10):p1–14. Masek J, Osancova K, Slabochova Z, Hejda S, Hatle J. Epidemiology and pathogenesis of obesity. Ceska Gynekol. 1962;16:p223–9. Heymsfield SB, Wadden TA. Mechanisms, Pathophysiology, and Management of Obesity. N Engl J Med. 2017;376(3):p254–66. Gruzdeva O, Borodkina D, Uchasova E, Dyleva Y, Barbarash O. Leptin resistance: Underlying mechanisms and diagnosis. Diabetes, Metab Syndr Obes Targets Ther. 2019;12:p191–8. Poulimeneas D, Anastasiou CA, Santos I, Hill JO, Panagiotakos DB, Yannakoulia M. Exploring the relationship between the Mediterranean diet and weight loss maintenance: The MedWeight study. Br J Nutr. 2020;124(8):p874–80. Foster MT, Pagliassotti MJ. Metabolic alterations following visceral fat removal and expansion. Adipocyte. 2012;1(4):p192–9. Wu H, Ballantyne CM. Metabolic Inflammation and Insulin Resistance in Obesity. Circ Res. 2020:p1549–64. Vázquez-Jiménez JG, Roura-Guiberna A, Jiménez-Mena LR, Olivares-Reyes JA. Role of free fatty acids on insulin resistance. Gac Mexico. 2019;153(7):p773–83. Agnoli C, Sieri S, Ricceri F, Giraudo MT, Masala G, Assedi M, et al. Adherence to a Mediterranean diet and long-term changes in weight and waist circumference in the EPIC-Italy cohort. Nutr Diabetes. 2018;8(1). Williamson G, Sheedy K. Effects of polyphenols on insulin resistance. Nutrients. 2020;12(10):p1–19. Bodnaruc AM, Prud’Homme D, Blanchet R, Giroux I. Nutritional modulation of endogenous glucagon-like peptide-1 secretion: A review. Nutr Metab. 2016;13(1):p1–16. Washudi, Hariyanto T. BIOMEDIK DASAR. Kementrian Kesehatan Republik Indonesia. 2016. Sherwood L. Introduction to Human Physiology International Edition. Eight Edition. Brooks/Cole Cengage Learning. Virginia: Yolanda Cossio; 2013. Buchanan A, Villani A. Association of adherence to a Mediterranean diet with excess body mass, muscle strength and physical performance in overweight or obese adults with or without type 2 diabetes: Two cross-sectional studies. Healthc. 2021;9(10). Singh M, Thrimawithana T, Shukla R, Adhikari B. Managing obesity through natural polyphenols: A review. Futur Foods. 2020;100002. Battineni G, Sagaro GG, Chintalapudi N, Amenta F, Tomassoni D, Tayebati SK. Impact of Obesity-Induced Inflammation on Cardiovascular Diseases (CVD). Int J Mol Sci. 2021;22(9). McCarthy HD, Samani-Radia D, Jebb SA, Prentice AM. Skeletal muscle mass reference curves for children and adolescents. Pediatr Obes. 2014;9(4):p249–59. Volpi E, Nazemi R, Fujita S. Muscle tissue changes with aging. Curr Opin Clin Nutr Metab Care. 2014;7(4):p405–10. Nikawa T, Ulla A, Sakakibara I. Polyphenols and their effects on muscle atrophy and muscle health. Molecules. 2021;26(16). Kelaiditi E, Jennings A, Steves CJ, Skinner J, Cassidy A, MacGregor AJ, et al. Measurements of skeletal muscle mass and power are positively related to a Mediterranean dietary pattern in women. Osteoporos Int. 2016;27(11):p3251–60. Salucci S, Falcieri E. Polyphenols and their potential role in preventing skeletal muscle atrophy. Nutr Res. 2020;74:p10–22.